Palm Oil Fuel Ash, Garnet Waste and Sawdust as Modified Asphalt Mixture: A Critical Review - Wan Noor Hin, Mior Sani; Putra Jaya, Ramadhansyah; Khairil Azman, Masri (IOP Publishing, 2024)
The addition of palm oil fuel ash (POFA), garnet waste, and sawdust as a modified asphalt binder and mixture for paving materials show that recycling materials from industrial and agricultural waste have been implemented with environmental concern, increasing the proper handling of this waste product. The use of POFA, garnet waste, and sawdust as a modifier to improve the properties of binder and mixture is critically evaluated in this study. The review focuses on the evaluation of POFA, garnet waste, and sawdust in asphalt binder and mixture modification. In essence, the combination of POFA, garnet waste, and sawdust offer a promising waste materials potential to enhance the rheological and mechanical performance of the modified binder and mixture. The use of this modification in the binder and mixture is expected to improve performance and be on par with the traditional asphalt binder and mixture.